Incidence of pain flare following palliative radiotherapy for symptomatic bone metastases: multicenter prospective observational study. Issue 1 (December 2015) - Gomez-Iturriaga, Alfonso; Cacicedo, Jon; Navarro, Arturo; Morillo, Virginia; Willisch, Patricia; Carvajal, Claudia; Hortelano, Eduardo; Lopez-Guerra, Jose; Illescas, Ana; Casquero, Francisco; Del Hoyo, Olga; Ciervide, Raquel; et al.
Abstract Background Palliative radiotherapy (RT) is an effective treatment for symptomatic bone metastases. Pain flare, a transient worsening of the bone pain after RT, has been described in previous reports with different incidence rates. The aim of the study was to prospectively evaluate the incidence of pain flare following RT for painful bone metastases and evaluate its effects on pain control and functionality of the patients. Methods Between June 2010 and June 2014, 204 patients were enrolled in this study and 135 patients with complete data were evaluable. Pain flare was defined as a 2- point increase in worst pain score as compared with baseline with no decrease in analgesic intake or a 25 % increase in analgesic intake as compared with baseline with no decrease in worst pain score. All pain medications and worst pain scores were collected before, daily during, and for 10 days after RT. The Brief Pain Inventory (BPI) was filled out on the pretreatment and at the 4 weeks follow-up visit. Results There were 90 men (66.7 %) and 45 women (33.3 %). Mean age was 66 years (SD 9.8). The most common primary cancer site was lung in 42 patients (31.1 %), followed by prostate in 27 patients (20.0 %). Forty-two patients (31.1 %) patients received a single fraction of 8 Gy and 83 (61.5 %) received 20 Gy in five fractions. The overall pain flare incidence across all centers was 51/135 (37.7 %). The majority of pain flares occurred on days 1–5 (88.2 %). The mean duration of the pain flare was 3 days (SD: 3). There were no significant relationships between the occurrence of pain flare and collected variables. All BPI items measured four weeks after end of RT showed significant improvement as compared with pretreatment scores (p < 0.001). No significant differences in BPI time trends were found between patients with and without flare pain. Conclusion Pain flare is a common event, occurring in nearly 40 % of the patients that receive palliative RT for symptomatic bone metastases. This phenomenon is not a predictor for pain response.